2019
DOI: 10.1016/j.ebiom.2018.11.059
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism of synaptic and cognitive impairments mediated via microRNA-30b in Alzheimer's disease

Abstract: BackgroundIt is widely accepted that cognitive and memory deficits in Alzheimer's disease (AD) primarily result from synaptic failure. However, the mechanisms that underlie synaptic and cognitive dysfunction remain unclear.MethodsWe utilized molecular biology techniques, electrophysiological recordings, fluorescence in situ hybridization (FISH), immuno- and Golgi-staining, chromatin immunoprecipitation (CHIP); lentivirus (LV)-based microRNA overexpression and ‘sponging’, and behavioral tests to assess upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 77 publications
0
61
0
Order By: Relevance
“…In the study of AD patients, miR-34a/p73 expression is found to be remarkably increased in hippocampal tissues, which participates in modulating synaptic activity by lessening synaptotagmin-1 expression (44). Through microRNA microarray screening analysis, the significant up-regulation of miR-30b in the brain of AD patients and transgenic mice is observed (45). The overexpression of miR-30b in hippocampal tissues can jeopardize synaptic structure and function of hippocampal neurons; in turn, can cause the deficits in cognitive function in normal wild type animals.…”
Section: Microrna-mediated Synaptic Dysfunction In Admentioning
confidence: 99%
“…In the study of AD patients, miR-34a/p73 expression is found to be remarkably increased in hippocampal tissues, which participates in modulating synaptic activity by lessening synaptotagmin-1 expression (44). Through microRNA microarray screening analysis, the significant up-regulation of miR-30b in the brain of AD patients and transgenic mice is observed (45). The overexpression of miR-30b in hippocampal tissues can jeopardize synaptic structure and function of hippocampal neurons; in turn, can cause the deficits in cognitive function in normal wild type animals.…”
Section: Microrna-mediated Synaptic Dysfunction In Admentioning
confidence: 99%
“…In a mouse model of peripheral inflammation induced by pancreatic ductal adenocarcinoma (PDAC), EVs containing miR-30 are up-regulated and abrogate tumor-suppressing mechanisms [134]. Interestingly, cerebral miR-30 directly impairs synaptic transmission and plasticity of hippocampal neurons [135]. The release of tumor-derived miR-30 into the circulation and subsequent localization to the CNS could provide an uninterrupted mechanism of tumor-induced cognitive impairment.…”
Section: Theory Of Soluble Tumor Factors’ Ability To Communicate Wmentioning
confidence: 99%
“…miRNAs are short (18-23 nt) non-coding RNAs, which bind predominantly to the 3′UTRs of complementary mRNAs and regulate their expression at the post-transcriptional level [22]. Extensive studies on neurodegenerative diseases have demonstrated important roles for miRNAs in the pathology of these diseases [23][24][25]. The first miRNA involved in FRDA pathogenesis was reported by Kelly et al [26], who found, based on in silico studies, that miRNA-155 may be involved in a cardiac phenotype of FRDA.…”
Section: Introductionmentioning
confidence: 99%